Rapid mild macrocyclization of depsipeptides under continuous flow: total syntheses of five cyclodepsipeptides. Issue 23 (26th October 2022) - Liao, Jingyuan; Jia, Xuelei; Wu, Fusong; Huang, Junrong; Shen, Guifu; You, Hengzhi; Chen, Fen-Er
Abstract : A systematic investigation of the flow macrocyclization approaches for five destruxin analogues natural products at three different cyclization point has been reported. Abstract : The total synthesis of five natural products destruxin B, pseudodestruxin B, isaridin A, cladoamide A, and cladoamide B was accomplished. These depsipeptides were synthesized though a flow macrocyclization method from linear precursors, which were obtained by the solid-phase peptide synthesis (SPPS) method, and three different cyclization points (–CONHR, –CONR2, –COOR) were designed to improve the total yield. In this study, the first examples of macrolactonization under flow were reported, and all 5 macrocyclizations were found to be significantly accelerated from hours to minutes. In addition, selective control of trans / cis conformers at the –CONR2 cyclization point was revealed to be possible by employing suitable coupling reagents for macrolactamization.